Budżetowanie kosztów w ośrodkach odpowiedzialności w OSM Lubin - Maszczak, Teresa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article discusses issues and problems connected with dairy production budgeting costs. Budgeting constitutes an important tool of unit management in a competitive market. It outlines a framework for the planning of annual activity and predicting their direct effects. Simultaneously, it allows for the understanding of unexpected consequences as they appear. Making use of such a budgeting method, managers are able to directly influence the reduction of production costs and the improvement of financial results. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 220-249